Home Industry Soybean Milk Marketing Assistance - Ifa, Khoirul (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
This activity aims to assist product packaging innovation, innovate flavors and product variances, and provide marketing assistance. The approach offered for solving partner problems consists of surveys, interviews, practice, monitoring and evaluation. The product innovation and marketing assistance that has been proposed has succeeded in making soy milk packaging more attractive and varied, while the innovation in the taste of soy milk also makes the product taste different from before, marketing assistance makes partners more competitive and can expand the market This activity is fully supported by the soy milk business group, because it succeeded in providing new ideas in terms of providing packaging design, flavor variance innovation and product marketing.